The Legal Position of The Feasibility Study in Hospital Development Under Law Number 17 of 2023 on Health - I Wayan Gede Subawa; I Putu Harry Suandana Putra; Ni Nyoman Putri Purnama Santhi; Ni Putu Yuliana Kemalasari (Westscience Press, 2026)
This study aimed to analyze the legal framework governing the preparation of a feasibility study for hospital development under Law Number 17 of 2023 on Health and its implementing regulations, to examine the position of needs and feasibility assessment in the feasibility study as the basis for licensing and hospital establishment, and to analyze the legal consequences of hospital development carried out without a feasibility study that complies with statutory requirements. This research employed normative legal research using statutory, conceptual, and analytical approaches, with primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that a feasibility study in hospital development functions as a substantive basis for licensing, an administrative control instrument, and a means of protecting public interest, since none of the regulations examined explicitly defines feasibility study as a mandatory legal document, leaving a normative gap regarding its definition, methodology, and evaluation mechanism. Hospital development without a feasibility study that complies with legal requirements may result in rejection or revocation of licenses, legal liability of the organizer, civil losses, and disruption of the protection of patients' and society's rights. The study concludes that a feasibility study must be positioned as a legal compliance instrument that is comprehensively prepared before hospital development is carried out, and recommends that the government formulate a national technical standard covering its definition, scope, methodology, and evaluation mechanism.